A systematic review of randomised controlled trials of psychosocial interventions for acute mental health inpatients. (2nd August 2021) - Wainwright, Laura D; Haddock, Gillian; Dunster-Page, Charlotte; Berry, Katherine
Abstract : Background/Aims: Inpatient wards provide an opportunity to intervene with medical, psychological and social care to contain distress and prevent future relapse. However, they have been criticised for an over-reliance on medication and risk management with limited psychosocial interventions. The aim of this study was to investigate clinical trials of psychosocial interventions for inpatients to identify interventions that are effective at improving quality of life, symptoms or patient functioning. Methods: An electronic search of six databases was conducted for papers published from 1806 up until February 2017. A total of 18 randomised controlled trials was identified in which outcomes for symptoms, quality of life or functioning were reported. Results: Overall, 15 trials showed a statistically significant result for at least one outcome. Seven categories were identified from the 18 studies, at least one in each category was found to be effective for symptoms, quality of life or functioning. The majority were effective (15 out of 18). Conclusions: Given that the methodological quality was generally low and number of randomised controlled trials were small, it is difficult to draw definitive conclusions. Recommendations include more and repeated trials using rigorous methods of testing and reporting.